Ternary combined industrial wastes for non-fired brick. Issue 2 (3rd April 2022) - Islam, G M Sadiqul; Shubbar, Ali A.; Sarker, Sudipta; Sadique, Monower
ABSTRACT: The demand for bricks in South Asia is increasing significantly due to growth in the construction sector. Bricks produced using traditional firing technique and fertile clay contribute significantly to some of the worst air pollution in the world. Therefore, the utilisation of other environment-friendly alternative to conventional bricks is considered an urgent need to conserve a clean environment and help in saving its fertile soil. This research aimed to explore geopolymerisation technique with ternary combined industrial waste/by-products as binders including high volume Ladle Furnace Slag (LFS), Fly ash and Ground Granulated Blast Furnace Slag (GGBS) to produce non-fired and clay-free brick alternatives. The first two byproducts are locally produced in the related iron and power industry while GGBS are being imported by the cement industry. The results indicated that all the prepared samples conform to the minimum compressive strength requirement of 20.7 MPa and maximum water absorption rate of 17% for common brick with severe weathering as per ASTM C62. This highly promising performance pronounced the use of locally available high volume LFS and other industrial waste/by-products materials in non-fired building block production to achieve a cleaner, environmental-friendly sustainable society as well as a sustainable route for industrial waste management.